Potential of graphene-based materials to combat COVID-19: properties, perspectives, and prospects. (December 2020) - Srivastava, A.K.; Dwivedi, N.; Dhand, C.; Khan, R.; Sathish, N.; Gupta, M.K.; Kumar, R.; Kumar, S.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a new virus in the coronavirus family that causes coronavirus disease (COVID-19), emerges as a big threat to the human race. To date, there is no medicine and vaccine available for COVID-19 treatment. While the development of medicines and vaccines are essentially and urgently required, what is also extremely important is the repurposing of smart materials to design effective systems for combating COVID-19. Graphene and graphene-related materials (GRMs) exhibit extraordinary physicochemical, electrical, optical, antiviral, antimicrobial, and other fascinating properties that warrant them as potential candidates for designing and development of high-performance components and devices required for COVID-19 pandemic and other futuristic calamities. In this article, we discuss the potential of graphene and GRMs for healthcare applications and how they may contribute to fighting against COVID-19. Graphical abstract: Image 1 Highlights: Potential of graphene-based materials to combat viral diseases, and virus spread. The properties of graphene-based materials for healthcare applications. Various graphene-based biosensor technologies for the diagnosis of viruses. Graphene-based nanofoams and 3D printed components for protective equipment's. Graphene-based antiviral surface coatings for high touch surfaces.